PERAN PENDIDIKAN AGAMA ISLAM (PAI) DALAM MENCEGAH TIMBULNYA JUVENILE DELIQUENCY - Mia Mia; M. Faiz Maulana; Alina Audia; Muhammad Alba Zahrouddin (UIN Sunan Kalijaga, 2021)
The swift current of globalization has a negative influence on the community which has an impact on the social style or behavior of each individual in society. This impact is very vulnerable for adolescents so that deviant behavior arises which is commonly called juvenile delinquency. At the same time, education plays a role in creating a learning atmosphere and an active learning process to develop students' potential. The role of Islamic religious education is the topic raised in this paper. The method used in writing this article uses a qualitative descriptive approach, and the type of research used is library research, where the results of the qualitative research are descriptive data in the form of written words. This article covers several things including Islamic religious education, juvenile delinquency, the factors that cause juvenile delinquency and the role of Islamic religious education in preventing juvenile delinquency. The results of this study, there are several steps that can be taken so that teenagers and students in general are able to fortify themselves with strong faith to avoid juvenile delinquency, of course the involvement of all policy makers is also a supporting factor.